Women in the STEM Sector - Jedwab, Jack (2016)
Gender-based analysis (hereafter GBA) is defined by Status of Women Canada “a method for examining how an issue is affected by sex, gender, and other intersecting identity factors. It involves examining disaggregated data, as well as social, economic, and cultural conditions and norms.” (GBA: Gender-Based Analysis Plus, SWC 2015). The goal of this project is to conduct a gender-based analysis of the barriers and opportunities faced by women in the Science, Technology, Engineering and Math sector (hereafter STEM), notably when it comes to advancement in their careers. GBA uses sex and gender as entry points to examining an issue, while situating these factors across various identities and experiences. In this report, we focus on the STEM sector, a highly educated group of women from diverse backgrounds, in the Montreal area. We examine this group in relationship to the broader community, as well as focusing on differences across this group, namely in terms of experience within the field.

Report on the Proceedings of the Advancing Women in STEM Community Leaders Forum & Strategic Recommendations - Association for Canadian Studies (ACS) (Youth Employment Services (YES), 2018)
YES Montreal is currently leading one of 20 initiatives funded by Status of Women to advance gender equality in Canada. Advancing Women in STEM is a three-year grant project (2017-2020) that aims to address and identify solutions to a number of systemic challenges hindering women’s retention and access to leadership positions within the STEM industry. This initiative follows from two previous ones; in the inaugural project (2012-2015), YES conducted three annual gender-based analyses of Quebec’s technology sector and in the second project (2015-2017) developed a tailored mentorship model for women in Montreal’s STEM industry. The overarching goal of the Advancing Women in STEM project is to create systemic change within STEM companies by shifting institutional practices to promote inclusivity and leadership opportunities for women. Successfully achieving this goal is dependent on the collaboration and support of industry and community leaders, particularly the project’s advisory committee that consists of fifteen outstanding women leaders who are highly engaged in this initiative and its outcomes.